2023
DOI: 10.3390/en16196973
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Materials for Complex Components in Ammonia/Hydrogen Gas Turbines: A Critical Review

Mustafa Alnaeli,
Mohammad Alnajideen,
Rukshan Navaratne
et al.

Abstract: This article reviews the critical role of material selection and design in ensuring efficient performance and safe operation of gas turbine engines fuelled by ammonia–hydrogen. As these energy fuels present unique combustion characteristics in turbine combustors, the identification of suitable materials becomes imperative. Detailed material characterisation is indispensable for discerning defects and degradation routes in turbine components, thereby illuminating avenues for improvement. With elevated turbine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 204 publications
1
0
0
Order By: Relevance
“…Their findings revealed that undiluted H 2 leads to unacceptable emission levels, necessitating a significant reduction in SFT to achieve emissions comparable to power industry standards. Similar observations have been reported when co-firing H 2 mixtures with other fuels, for instance, in reciprocating engines [21,22] and heating boilers [23,24]. As shown in the literature review, there are contradictions regarding the effect of H 2 content in fuel on nitrogen oxide emissions.…”
Section: Introductionsupporting
confidence: 76%
“…Their findings revealed that undiluted H 2 leads to unacceptable emission levels, necessitating a significant reduction in SFT to achieve emissions comparable to power industry standards. Similar observations have been reported when co-firing H 2 mixtures with other fuels, for instance, in reciprocating engines [21,22] and heating boilers [23,24]. As shown in the literature review, there are contradictions regarding the effect of H 2 content in fuel on nitrogen oxide emissions.…”
Section: Introductionsupporting
confidence: 76%